Contourites in the Upper Jurassic-Lower Cretaceous Vaca Muerta Formation: Implications for the depositional model and sequence stratigraphy - Paz, Maximiliano (2022)
Fil: Paz, Maximiliano.University of Saskatchewan, Department of Geological Sciences, 114 Science Place, S7N 5E2 Saskatoon, Canada